The status quo of early burn wound excision: Insights from the German burn registry - Glaser, Julia; Ziegler, Benjamin; Hirche, Christoph; Tapking, Christian; Haug, Valentin; Bliesener, Björn; Kilian, Katja; Kneser, Ulrich; Hundeshagen, Gabriel (Burns, 2021)
Background: There is a common, well-known and established recommendation to excise burn wounds within 24-72 h in order to mitigate the systemic inflammatory and immunomodulatory response, shorten length of hospitalization through early grafting and optimize patient survival. Despite this apparent consensus, surprisingly few systematic studies have evaluated the actual adherence to this practice and its implications on patient outcomes. In this registry study, we sought to objectify the current status of early burn wound excision, its influencing factors and impact on patient outcomes for all German burn centers. Methods: The German burn registry ('Deutsches Verbrennungsregister') was queried for 3 consecutive years for all patients, who received at least one surgical intervention. Patients were stratified based on whether the first surgical procedure was performed early (EE, within 72 h) or late (LE, after 72 h) post-burn. Descriptive statistics and univariate regressions were performed to quantify fraction of EE vs. LE and to evaluate factors which might favor one over the other(i.e. age, inhalation injury, burn severity by total body surface area (TBSA), scald vs. other burns, obesity, time of admission). Key patient outcomes were analyzed for each group (i.e. mortality, length of hospitalization, number of surgeries) and multifactorial regression analyses were carried out to model the impact of EE on mortality. Statistical significance was accepted at p < 0.05. Results: After initial screening, 1494 complete records were included for final analysis and were stratified into EE and LE. Only 670 (44%) underwent EE within 72 h. Increasing TBSA burned (i.e. [TBSA > 30%]: 53.8% EE, [TBSA < 30%]: 43.5% EE, p < 0.01) and admission on a weekday between Sunday and Wednesday were associated with higher probability of EE (51.5% EE) versus Thursday to Sunday (37.3%, p < 0.001). Age, inhalation injury, cause of burn, and obesity had no effect on EE vs. LE. Patients with EE had significantly shorter median lengths of hospitalization (EE: 18 d, LE: 21 d, p < 0.01). The median number of operations was comparable for both groups. Gross mortality appeared higher in the EE group, but turned out to be comparable to LE after correction for age, TBSA and sex in multifactorial regression analysis. Conclusion: Despite apparent consensus among burn physicians, early excision of burn wounds is performed in less than 50% of cases in German burn centers. The relationship of EE to TBSA burned is expected and clinically sound, while a dependence on admission weekday raises administrative and infrastructural questions, especially when patients who receive EE have significantly shorter hospital stays. More analyses from other burn repositories are needed to compare and benchmark the international status quo of early burn wound excision. (C) 2021 Elsevier Ltd and ISBI. All rights reserved.
Gesehen am 06.10.2021